The Effect of Nurses Stressogenic Factors and Psychoemotic State on Care Cooperation - Šleinytė, Ieva; Mikaliūkštienė, Aldona (Slauga. Mokslas ir praktika, 2022)
Nurses inevitably experience stress in their work, which affects their psycho-emotional state. Complicated business and interpersonal relationships, conflicts with colleagues, patients and their relatives, high workload, difficulty in decision-making, nursing of dying patients, working in pandemic conditions cause stress, anxiety, fear, sleep disturbances, exhaustion and depression, which affect the psycho-emotional state of nurses and cooperation between them. Cooperation between nurses is important not only for the quality of work of the nurses themselves, but also for the staff of other health care institutions and for the well-being of patients. The aim of the research - to analyze the scientific literature on the nurses stress experience at work, their emotional state and their impact on mutual cooperation. Research methods: systematic search of articles in PubMed, Cochrane ClinicalKey, BMJ Best Practice, ScienceDirect and Google Scholar databases. The results showed that stress and psychoemotional status of nurses are related and affect their cooperation. As a result of constant stress, most nurses experience both physical and psychological health problems, which affect teamwork.